Balinese Women’s Motivation for Pursuing Higher Education in Tourism Study Programs - Putu Sucita Yanthy; Sylvine Pickel-Chevalier (Pusat Kajian Bali Universitas Udayana, 2021)
The number of Balinese women taking tourism education at various levels appears to be increasing in line with the development of tourism education institutions and the tourism industry in Bali. This article analyzes the motivation of Balinese women in pursuing higher education in tourism, starting from the diploma level to the doctoral program. By applying a qualitative method, this article collects data through interviews with 30 Balinese women who have taken tourism education at various levels. The results show that Balinese women are motivated to take tourism education for several reasons, including the motivation to get a job in the tourism sector, they have families who work in the tourism sector, and they live in Bali which has more job opportunities in the tourism sector. By taking tourism education, Balinese women who were informants in this study proved that they had found better jobs and career opportunities in the tourism industry. Their experiences have also become a source of inspiration for other Balinese women to take the same career path.